Glycosylation‐deficient mutations in tissue‐nonspecific alkaline phosphatase impair its structure and function and are linked to infantile hypophosphatasia. (22nd February 2016) - Komaru, Keiichi; Satou, Yasuhito; Al‐Shawafi, Hiba A.; Numa‐Kinjoh, Natsuko; Sohda, Miwa; Oda, Kimimitsu
Abstract : Tissue‐nonspecific alkaline phosphatase (TNSALP) is a membrane glycoprotein with a proposed role in bone mineralization. Indeed, mutations in TNSALP have been identified in patients with hypophosphatasia (HPP), a genetic disease characterized by hypomineralization of bone and teeth and a deficiency in serum ALP activity. TNSALP has five potential N‐glycosylation sites at N140, N230, N271, N303 and N430 by standard nomenclature. A mutation at one of these sites, N430, was recently detected in a patient with infantile HPP. Using site‐directed mutagenesis, we demonstrated that TNSALP has five N ‐glycans in transfected COS‐1 cells and that individual single N ‐glycan deletion mutants of TNSALP retain the dimeric structure required for ALP activity, excluding the possibility that any single N ‐glycan plays a vital role in the structure and function of TNSALP. However, we found that TNSALP (N430Q) and TNSALP (N430E) mutants, but not a TNSALP (N430D) mutant, failed to form dimers. The TNSALP (N430S) mutant linked to infantile HPP was glycosylation‐defective and unable to dimerise, similar to TNSALP (N430Q) and TNSALP (N430E) mutants; therefore, TNSALP (N430S) was established as a severe allele without strong ALP activity. By contrast to individual single N ‐glycan deletion mutants, TNSALP devoid of all five N ‐glycans was present to a much lesser extent than wild‐type TNSALP in transfected cells, possibly reflecting its instability. A comprehensive analysis of a series of multiple N ‐glycan depletion mutants in TNSALP revealed that three N ‐glycans on N230, N271 and N303 were the minimal requirement for the structure and function of TNSALP and a prerequisite for its stable expression in a cell. Abstract : Role of N‐glycan in tissue‐nonspecific alkaline phosphatase (TNSALP) was investigated using site‐directed mutagenesis. Any single N‐glycan did not play an essential role for structure and function of TNSALP, though three N‐glycans on N230, N271, and N303 were the minimal requirement for the structure and function of TNSALP and a prerequisite for its stable expression in a cell.